2017
DOI: 10.1021/jacs.6b10651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interfacial Molecular Orientation on Power Conversion Efficiency of Perovskite Solar Cells

Abstract: A wide variety of charge carrier dynamics, such as transport, separation, and extraction, occur at the interfaces of planar heterojunction solar cells. Such factors can affect the overall device performance. Therefore, understanding the buried interfacial molecular structure in various devices and the correlation between interfacial structure and function has become increasingly important. Current characterization techniques for thin films such as X-ray diffraction, cross section scanning electronmicroscopy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 77 publications
3
85
0
Order By: Relevance
“…It should be mentioned that such a pronounced increasing amplitude has seldom been reported for the HTM/perovskite interfacial optimization, and the J SC and PCE values of DTB device are the highest values ever released for the PSCs based on dopant‐free organic HTMs and the mesoporous PSCs based on dopant‐free polymeric HTMs, respectively (Tables S3 and S4, Supporting Information). Moreover, this is the first report that the unusual edge‐on orientation of polymer chains is realized for highly efficient polymers according to our knowledge …”
Section: Photovoltaic Properties Of the Optimized Pscs Based On Dtb Amentioning
confidence: 79%
See 2 more Smart Citations
“…It should be mentioned that such a pronounced increasing amplitude has seldom been reported for the HTM/perovskite interfacial optimization, and the J SC and PCE values of DTB device are the highest values ever released for the PSCs based on dopant‐free organic HTMs and the mesoporous PSCs based on dopant‐free polymeric HTMs, respectively (Tables S3 and S4, Supporting Information). Moreover, this is the first report that the unusual edge‐on orientation of polymer chains is realized for highly efficient polymers according to our knowledge …”
Section: Photovoltaic Properties Of the Optimized Pscs Based On Dtb Amentioning
confidence: 79%
“…Accordingly, both the bulk of charge‐transporting material and its interface with the perovskite layer are crucial to the performance of PSCs; however, the latter one was primarily optimized by introducing additional materials as stated above, and those highly efficient charge‐transporting materials that could simultaneously serve as interfacial optimizers were rarely reported and only limited to the function of defect passivation but without charge extraction . Recently Xiao et al found that an edge‐on orientation where the π–π stacking direction is in parallel to the perovskite layer showed a superior photovoltaic performance over the face‐on one for the homopolymer polythiophene based PSCs mainly due to its higher charge‐extracting ability. Although this edge‐on orientation could favor the hole‐transfer across the HTM/perovskite interface, the PCE it yielded was still lower than 14% .…”
Section: Photovoltaic Properties Of the Optimized Pscs Based On Dtb Amentioning
confidence: 99%
See 1 more Smart Citation
“…The interfaces of inorganic fluorides have been regarded as model systems for exploring many important reactions such as water‐mineral interactions and fluorine dissolution. [ 4c,5 ] Although the fluoride can be regarded as chemically stable in aqueous solution, slight dissolution of still occurs unless solubility equilibrium is achieved. Moreover, the hydration energy of fluoride (F − ) is much smaller that the metal ions, thus preferential leakage of F − would occur at the fluoride/water interface and more F − ions would be dissolved that the metal ions at solubility equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…The sum frequency generation (SFG) vibrational spectroscopy, a second‐order nonlinear optical technique, has been proved to be powerful for probing the interfacial molecules in view of its inherent interface selectivity and high sensitivity. [ 4 ] In this work, combined in situ spectroscopies based on SFG and photoluminescence (PL) characterization were adopted to reveal the unprecedented effect of particle moving to the interfacial adsorption of colloidal fluoride nanocrystals in great detail. Comparative results of the proof‐of‐concept experiments for the ligand‐free NaYF 4 :Yb,Er upconverting (UC) nanocrystals reveal that the particle moving in aqueous solution reversibly alter the surface charge.…”
Section: Introductionmentioning
confidence: 99%